2022
DOI: 10.1002/fsn3.2952
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of chlorogenic acid on isoflurane‐induced cognitive impairment of aged mice

Abstract: Postoperative cognitive dysfunction (POCD) is characterized by impairment in cognitive functions in patients following anesthesia and surgery. Chlorogenic acid (CGA) is a plant‐derived compound possessing numerous bioactive properties. The aim of this study was to investigate the therapeutic potential of CGA in isoflurane (ISO)‐induced cognitive dysfunction of aged mice, and further identify the mechanisms involved in the protective effects of CGA. A total of 80 male C57BL/6 mice, 20‐month‐old, were randomly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Chlorogenic acid (~17.8% of the total constituents of Pi infusion) is a phenolic acid, which is an ester of caffeic acid and quinic acid [24]. It has been ascribed neuroprotective, anti-inflammatory, and antioxidant effects [24,52,53] and reported to prevent cognitive decline and neuronal damage in the hippocampus, and to protect against cognitive impairment in aged mice [54,55]. Chlorogenic acid was shown to regulate the oxidative stress-related Nrf2 pathway [56] and to stimulate the CREB pathway [53].…”
Section: Discussionmentioning
confidence: 99%
“…Chlorogenic acid (~17.8% of the total constituents of Pi infusion) is a phenolic acid, which is an ester of caffeic acid and quinic acid [24]. It has been ascribed neuroprotective, anti-inflammatory, and antioxidant effects [24,52,53] and reported to prevent cognitive decline and neuronal damage in the hippocampus, and to protect against cognitive impairment in aged mice [54,55]. Chlorogenic acid was shown to regulate the oxidative stress-related Nrf2 pathway [56] and to stimulate the CREB pathway [53].…”
Section: Discussionmentioning
confidence: 99%
“…Although none of them has proven a significant benefit in preventing postoperative cognitive impairments, a possible neuroprotective effect was attributed to propofol [77]. As for volatile anesthetics, there are some studies which suggest a favorable cognitive outcome when using volatile agents like sevoflurane or desflurane, or at least indicate them to be a safer alternative for patients with preexisting cognitive disorders [66,[78][79][80]. Despite the fact that the current trend in anesthesia favours opioid-free anesthesia, there is no published evidence of the impact of this technique on neurocognitive impairment [81].…”
Section: Current Anesthetic Strategies For Preventing Postoperative D...mentioning
confidence: 99%
“…The general public was exposed to fake news [27] and conspiracy theories [28], which generated technostress [29] and multitasking behavior [30]. The lack of clear public policies generated mental distress [31,32] and an urgency for self-care behaviors [33,34] including the use of unproven drugs [25,35,36] and medicinal plants [25,36] in part based on their knowledge and appreciation of plants containing bioactive 2 of 15 compounds [37][38][39][40][41][42][43][44][45][46][47][48]. It has been further reported that this has impacted the vaccination intention [49].…”
Section: Introductionmentioning
confidence: 99%